2011
DOI: 10.1111/j.1445-2197.2011.05884.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction: a systematic review of polyethylene terephthalate grafts

Abstract: There are surprisingly few studies reporting on LARS ligament outcomes. The literature has poor methodological quality. Short-term results for the LARS ligament appear good, with faster recovery times compared with autografts. Final short-term results are not significantly different from autograft. There is real concern that late failure and iatrogenic osteoarthritis may occur based on the results of other PET grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Hamido F. et al [11] presented the potential use of LARS™ as ligament support for undersized hamstrings, reporting good outcome after a mean follow-up of 45.2 months. In addition, the LARS™ system might be considered in a patient who needs fast recovery and understand all the possible complications and the high long-term failure rate [2]. Despite these findings the autologous graft remains still the "gold standard" of ACL reconstruction, with a lower rate of complications and re-ruptures, especially in younger patients [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamido F. et al [11] presented the potential use of LARS™ as ligament support for undersized hamstrings, reporting good outcome after a mean follow-up of 45.2 months. In addition, the LARS™ system might be considered in a patient who needs fast recovery and understand all the possible complications and the high long-term failure rate [2]. Despite these findings the autologous graft remains still the "gold standard" of ACL reconstruction, with a lower rate of complications and re-ruptures, especially in younger patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial ligaments became highly attractive for orthopaedic surgeons at that time due to the lack of donor side morbidity and the ability of early return to sport activities [2]. Accelerated rehabilitation, immediate knee stability and full weight bearing following surgery were feasible compared to biological grafts [3] thus leading to encouraging results in the short-term [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…More significantly, the subsequent in-growth of new bone into the graft has been observed during research, which underlines the method to be qualified as a more effective method in PET preparation for graft-bone healing capacity enhancement. 39 Above all, the SF+HAP coating prepared by biomimetic mineralization on the surface of PET possesses the benefits of simplicity in manufacturing, high cellular and tissue induction, and also effective osteogenesis facilitation. Its osteoinduction and osteoconduction are better than traditional materials by creating a relatively more natural microenvironment during the boneformation process.…”
mentioning
confidence: 99%
“…One such example in the 1980s and early 1990s was the use of synthetic artificial ligaments for ACL reconstruction that became highly attractive for orthopaedic surgeons as a means of avoiding the potential drawbacks associated with autografts and allografts [10]. Theoretically, artificial ligaments allow for a more aggressive rehabilitation compared to biologic grafts and provide a quick recovery and early return to sports [15]. Despite these encouraging short-term clinical benefits, subsequent clinical research revealed that the use of artificial ligaments was also associated with poor patient outcomes and a high graft failure rate 1-2 years following placement.…”
Section: Quality Of Scientific Evidencementioning
confidence: 99%